Back Cover: Selective Formation of Hägg Iron Carbide with g‐C3N4 as a Sacrificial Support for Highly Active Fischer–Tropsch Synthesis (ChemCatChem 21/2015). Issue 21 (31st October 2015) - Park, Hunmin; Youn, Duck Hyun; Kim, Jae Young; Kim, Won Yong; Choi, Yo Han; Lee, Young Hye; Choi, Sun Hee; Lee, Jae Sung
Abstract : The Cover shows the Fischer‐Tropsch synthesis reaction over iron‐based catalysts activated by graphitic carbon nitride (g‐C3 N4 ). In their Full Paper, Park, Youn et al. describe the considerably enhanced FTS activity and selectivity, attributed to the selective formation of Hägg carbide (χ‐Fe5 C2 ) on the g‐C3 N4, which facilitates the reduction and carburization of iron species. The improved reduction and carburization degree of iron on the g‐C3 N4 originates from the electron‐rich nitrogen sites and the defect sites of the g‐C3 N4 structure. More details can be found in the Full Paper by J. S. Lee et al. onpage 3488 in Issue 21, 2015 (DOI:10.1002/cctc.201500794 ).